2021
DOI: 10.7150/thno.53652
|View full text |Cite
|
Sign up to set email alerts
|

NAD+-boosting therapy alleviates nonalcoholic fatty liver disease via stimulating a novel exerkine Fndc5/irisin

Abstract: Rationale: Nicotinamide adenine dinucleotide + (NAD + )-boosting therapy has emerged as a promising strategy to treat various health disorders, while the underlying molecular mechanisms are not fully understood. Here, we investigated the involvement of fibronectin type III domain containing 5 (Fndc5) or irisin, which is a novel exercise-linked hormone, in the development and progression of nonalcoholic fatty liver disease (NAFLD). Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(30 citation statements)
references
References 43 publications
0
25
0
Order By: Relevance
“…In humans and mice with NAFLD, a reduced cellular availability of NAD+ resulted in higher fat content and alimentary NAD+ supplementation reversed the effect [ 61 , 62 ]. Low NAD+ levels may activate p53, thereby inducing cell cycle arrest [ 63 ].…”
Section: The Role Of Cellular Senescence In Fatty Liver Diseasementioning
confidence: 99%
“…In humans and mice with NAFLD, a reduced cellular availability of NAD+ resulted in higher fat content and alimentary NAD+ supplementation reversed the effect [ 61 , 62 ]. Low NAD+ levels may activate p53, thereby inducing cell cycle arrest [ 63 ].…”
Section: The Role Of Cellular Senescence In Fatty Liver Diseasementioning
confidence: 99%
“…However, CD38 inhibition could also be exploited in the treatment of other diseases resulting from depletion of NAD + and/or over production of ADO. Decreases in NAD + levels are associated with various metabolic diseases (diabetes, obesity, dyslipidemia and nonalcoholic fatty liver) 48,49 and in aging. [50][51][52] It also plays a major role in the immune response to infectious disease 53 including COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the maintenance of normal serum irisin concentrations would also be important for irisin to exert antioxidant effects in liver disease. Furthermore, Li and colleagues found that under lipid stress, the acetylation and ubiquitination of the Fndc5 protein were dramatically strengthened, which accelerated Fndc5 degradation and consequently decreased the serum irisin concentration [89]. Based on this finding, we hypothesized that deacetylation and deubiquitination of Fndc5 would reverse the irisin level reduction.…”
mentioning
confidence: 86%
“…It was speculated that SIRT2 was the deacetylase of Fndc5. Moreover, Li et al found that the K127/131 and K185/187/189 sites of Fndc5 were essential for the deacetylation activity of SIRT2 [89] (Figure 2). Lantier and colleagues demonstrated that the depletion of SIRT2 would cause abnormal mitochondrial biosynthesis, which might negatively influence the antioxidant effect of irisin [90].…”
mentioning
confidence: 99%